Carotid Atherosclerotic plaque instability and cognition determined by ultrasound-measured plaque strain in asymptomatic patients with significant stenosis - Dempsey, Robert J. (J Neurosurg, 2017)
OBJECTIVE: This article describes the use of ultrasound measurements of physical strain within carotid atherosclerotic plaques as a measure of instability and the potential for vascular cognitive decline, microemboli and white matter changes. METHODS: Asymptomatic patients with significant (>60%) carotid stenosis were studied for dynamic measures of plaque instability, presence of microemboli, white matter changes, and vascular cognitive decline as measured by normative controls and premorbid state. RESULTS: Although classically asymptomatic, these patients showed vascular cognitive decline. The degree of strain instability measured within the atherosclerotic plaque directly predicted vascular cognitive decline in these patients felt previously to be asymptomatic by classical criteria. Further, 26 % of patients showed microemboli, and patients had twice as much white matter hyperintensities as controls. CONCLUSIONS: These data show that physical measures of plaque instability are possible through interpretation of ultrasound strain data during pulsation which may be more clinically relevant than solely measuring degree of stenosis. The data also highlights the importance of understanding that the definition of symptoms should not be limited to motor, speech and vision but stresses the role of vascular cognitive decline in the pathophysiology of carotid atherosclerotic disease.